NANOTECHNOLOGIES AND BIOMEDICINE: NEW OPPORTUNITIES IN XXI CENTURY MEDICAL EDUCATION - Abdiyev Kh.E.; Dushabayev A.M.; Saidqulov J.; Fayzullayev Sh. (Uzbekistan Open Conference, 2025)
The article discusses the integration of nanotechnology and molecular biology achievements into 21st-century medical education. Methods for enhancing students’ practical skills using virtual laboratories and interactive simulation modules are analyzed.
Keywords: nanotechnology; biomedicine; medical education; virtual laboratory; simulation modules